Projected precipitation changes in South America: a dynamical downscaling within CLARIS - Anna A. Sorensson; Claudio G. Menéndez; Romina Ruscica; Peter Alexander; Patrick Samuelsson; Ulrika Willén (Meteorologische Zeitschrift, 2010)
Responses of precipitation seasonal means and extremes over South America in a downscaling of a climate change scenario are assessed with the Rossby Centre Regional Atmospheric Model (RCA). The anthropogenic warming under A1B scenario influences more on the likelihood of occurrence of severe extreme events like heavy precipitation and dry spells than on the mean seasonal precipitation. The risk of extreme precipitation increases in the La Plata Basin with a factor of 1.5-2.5 during all seasons and in the northwestern part of the continent with a factor 1.5-3 in summer, while it decreases in central and northeastern Brazil during winter and spring. The maximum amount of 5-days precipitation increases by up to 50 % in La Plata Basin, indicating risks of flooding. Over central Brazil and the Bolivian lowland, where present 5-days precipitation is higher, the increases are similar in magnitude and could cause less impacts. In southern Amazonia, northeastern Brazil and the Amazon basin, the maximum number of consecutive dry days increases and mean winter and spring precipitation decreases, indicating a longer dry season. In the La Plata Basin, there is no clear pattern of change for the dry spell duration.